Maintaing change : a personal relapse prevention manual - Eldridge, Hilary (SAGE Publications, Inc., 1998)
This user-friendly, step-by-step personal relapse prevention manual - designed to be used in conjunction with the Therapist Guide for Maintaining Change, also by Hilary Eldridge - focuses on the notion of control and taking responsibility for one's actions rather than on `cure'. The programme requires participants to be active in the change process, with the ultimate goal of being able to self-manage. · Purchasers of Maintaining Changee: A Personal Relapse Prevention Manual may photocopy individual exercises and handouts for use with their own client.